The Effectiveness of B Cells in CAR T Cell Therapy for B Cells Acute Lymphoblastic Leukemia - Haries, Elena M. D. P.; Abadi, Abadi (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Chimeric Antigen Receptor (CAR) T cell therapy has shown remarkable clinical outcomes in B cell Acute Lymphoblastic Leukemia (B-ALL). The treatment can utilize the immune system to recognize and kill leukemia cells through the CD19 antigen target. However, the CD19 antigen is also expressed on normal B cells, which can cause side effects in B cell aplasia. This study modiﬁes a mathematical model of the interaction between CAR T cells, leukemia cells, and normal B cells by introducing the assumption that leukemia cells follow logistic growth dynamics. Determined the equilibrium point and continues to analyze stability using linearization and the Routh-Hurwitz criterion. The analysis reveals four equilibrium points, including a state where leukemia cells grow at maximum capacity in the absence of CAR T cells. Bifurcation analysis shows the occurrence of both transcritical and subcritical Hopf bifurcations, with distinct patterns compared to previous models. A heteroclinic cycle was also identiﬁed, indicating that relapse may occur even after remission. The logistic growth and B cell progenitors not only shape remission and relapse dynamics but also explain the dual role of B cells in sustaining CAR T activation and causing complications such as Cytokine Release Syndrome (CRS). This provides new insights for understanding therapy outcomes and optimizing CAR T cell treatment strategies.